Third Ventricular and Interpeduncular Fossa Tubercular Abscess With Triventriculomegaly - Ventriculoscopic Surgical Management - Chowdhury, Forhad Hossain; Haque, Mohammod Raziul; Alam, Mohammod Sarwar Morshed (Journal of Medicine, 2013)
Intracranial tuberculomas are rather common lesions in developing world.Tuberculomas are usually located in cerebellum, basal ganglia and cerebral hemispheres, particularly in frontoparietal region.Less common sites include the corpus callosum, quadrigeminal plate,the cerebellopontine angle, the retro-orbital region, the anterior optic pathway and the supraseller region.The central nervous system (CNS) involvement comprises approximately 1015% of all tuberculous infections. Brain tuberculosis is usually parenchymal. Intraventricular tuberculosis is very rare and only little number of cases has been reported. Intraventricular tubercular abscess is further rarer. Here we report a case of third ventricular tubercular abscess with triventriculomegaly that was managed by ventriculoscopic drainage and third ventriculostomy though preoperative diagnosis & surgical planning was different. DOI: http://dx.doi.org/10.3329/jom.v14i1.11415 J MEDICINE 2013; 14 : 72-73